Correlation of Magnetic Resonance Imaging With Knee Anterolateral Ligament Anatomy: A Cadaveric Study. Issue 12 (16th December 2015) - Helito, Camilo Partezani; Helito, Paulo Victor Partezani; Bonadio, Marcelo Batista; Pécora, José Ricardo; Bordalo-Rodrigues, Marcelo; Camanho, Gilberto Luis; Demange, Marco Kawamura
Background: Anatomic and magnetic resonance imaging (MRI) studies have recently characterized the knee anterolateral ligament (ALL). So far, no study has focused on confirming whether the evaluated MRI parameters truly correspond with ALL anatomy. Purpose: To assess the validity of MRI in detecting the ALL using an anatomic evaluation as reference. Study Design: Descriptive laboratory study. Methods: A total of 13 cadaveric knees were subjected to MRI and then to anatomic dissection. Dissection was performed according to previous anatomic study methodology. MRIs were performed with a 0.6- to 1.5-mm slice thickness and prior saline injection. The following variables were analyzed: distance from the origin of the ALL to the origin of the lateral collateral ligament (LCL), distance from the origin of the ALL to its bifurcation point, maximum length of the ALL, distance from the tibial insertion of the ALL to the articular surface of the tibia, ALL thickness, and ALL width. The 2 sets of measurements were analyzed using the Spearman correlation coefficient (ρ) and Bland-Altman plots. Results: The ALL was clearly observed in all dissected knees and MRI scans. It originated anterior and distal to the LCL, close to the lateral epycondile center, and showed an anteroinferior path toward the tibia, inserting between the Gerdy tubercle and the fibular head, around 5 mm under the lateral plateau. The ρ values tended to increase together for all studied variables between the 2 methods, and all were statistically significant, except for thickness ( P = .077). Bland-Altman plots showed a tendency toward a reduction of ALL thickness and width by MRI compared with anatomic dissection. Conclusion: MRI scanning as described can accurately assess the ALL and demonstrates characteristics similar to those seen under anatomic dissection. Clinical Relevance: MRI can accurately characterize the ALL in the anterolateral region of the knee, despite the presence of structures that might overlap and thus cause confusion when making assessments based on imaging methods.